Operational risk management : best practices in the financial services industry - Chapelle, Ariane (West Sussex, United Kingdom : Wiley, 2019)
The author explores the range of operational risks such as information security, fraud or reputation damage and details how to put in place an effective program based on the four main risk management activities: risk identification, risk assessment, risk mitigation and risk monitoring. The book also examines some specific types of operational risks that rank high on many firms' risk registers.
Includes bibliographical references and index.
ne 23/08/2022
Loans
Keywords: Financial services industry; Banks and banking; Bank management; Financial risk management